Powder diffraction in Bragg–Brentano geometry with straight linear detectors. (1st April 2015) - Kriegner, Dominik; Matěj, Zdeněk; Kužel, Radomír; Holý, Václav
<x xml:space="preserve">Abstract</x> A common way of speeding up powder diffraction measurements is the use of one‐ or two‐dimensional detectors. This usually goes hand in hand with worse resolution and asymmetric peak profiles. In this work the influence of a straight linear detector on the resolution function in the Bragg–Brentano focusing geometry is discussed. Because of the straight nature of most modern detectors geometrical defocusing occurs, which heavily influences the line shape of diffraction lines at low angles. An easy approach to limit the resolution‐degrading effects is presented. The presented algorithm selects an adaptive range of channels of the linear detector at low angles, resulting in increased resolution. At higher angles the whole linear detector is used and the data collection remains fast. Using this algorithm a well behaved resolution function is obtained in the full angular range, whereas using the full linear detector the resolution function varies within one pattern, which hinders line‐shape and Rietveld analysis.